2008
DOI: 10.1109/tmag.2008.2002253
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties and Crystallographic Structure of Fe$_{3}$Pt Thin Films

Abstract: Fe 100 x Pt x (x = 20, 25, and 30) thin films with nominal thickness 50 nm were prepared by radio-frequency (RF) magnetron sputtering onto glass substrates. Crystallographic structure and magnetic properties of such films were investigated by varying Fe content, annealing temperature (400-700 C), and heating process. Crystallographic structure obtained by X-ray diffraction (XRD) indicated that ordering of 1 2 Fe 3 Pt phase takes place for Fe 75 Pt 25 postannealed above 400 C. Ordering parameter of the Fe 75 Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…As ligas relacionadas com a super-rede Fe 3 Pt apresentam características interessantes, tal como a transformação martensítica [43] e a magnetostricção gigante [44]. Recentemente, essas ligas têm atraído a atenção devido às excelentes propriedades magnéticas (magnetização de saturação 1.350 emu/cm 3 ) e adequação para aplicação de ímãs acoplados "soft-hard", especialmente em sistemas compostos por Fe 3 Pt (mole) /FePt (duro) [45]. Para estimar a quantidade de material depositado no substrato utilizamos a técnica de retroespalhamento Rutherford (RBS 5 ).…”
Section: Nanopartículas De Compostos Com Metais De Transiçãounclassified
“…As ligas relacionadas com a super-rede Fe 3 Pt apresentam características interessantes, tal como a transformação martensítica [43] e a magnetostricção gigante [44]. Recentemente, essas ligas têm atraído a atenção devido às excelentes propriedades magnéticas (magnetização de saturação 1.350 emu/cm 3 ) e adequação para aplicação de ímãs acoplados "soft-hard", especialmente em sistemas compostos por Fe 3 Pt (mole) /FePt (duro) [45]. Para estimar a quantidade de material depositado no substrato utilizamos a técnica de retroespalhamento Rutherford (RBS 5 ).…”
Section: Nanopartículas De Compostos Com Metais De Transiçãounclassified
“…Further annealing at relatively high temperatures leads to the complete disappearance of the BCC phase.The phase transformation for Fe 3 Pt requires further study, partially due to the inconsistency in the available literature. Both FCC[49] and BCC[50] phases were observed in as-deposited films, while the phase after annealing is greatly dependent on the annealing process[49], e.g., in-situ or post -annealing. In their rf magnetron sputtered films, Hsiao et al found that in-situ annealing leads to the formation of metastable FCT with coercivity 2.4 kOe, while post-annealing results in the L1 2 phase with lower coercivity[49]; the saturation magnetization also depends on the phase, FCT with lower M s and L 2 with higher M s[49].…”
mentioning
confidence: 99%